A new triterpene from Atalantia retusa merr - Ragasa, Consolacion Y. (Animo Repository, 2012)
Atalantia retusa Merr. is a rare Philippine endemic shrub which was reported to exhibit high antinociceptive and anti-inflammatory activities. The dichloromethane extract of the air-dried leaves of A. retusa afforded a new triterpene, retusenol (1), and friedelin (2), dischidiol (3), 5,7-dimethoxy-8- (3-methyl-2-oxybutyl)coumarin (4), humulene (5), and b-caryophyllene (6). The structures of 1 - 4 were elucidated by extensive 1D and 2D NMR experiments. Friedelin, a known analgesic and antiinflammatory drug, is an active principle of the shrub. Compounds 1 - 4 were tested for cytotoxicity against the human cancer lung adenocarcinoma A549, colon carcinoma HCT116 and the non-cancer Chinese hamster ovary AA8 using the MTT assay. Triterpenes 1 - 3 had no linear interpolation with HCT 116 and A549, thus the IC50 value could not be computed. This implied that these compounds did not exhibit any cytotoxic effect against these cell lines. Meanwhile, 4 exhibited moderate cytoxicity against A549, HCT 116 and AA8 with IC50 values of 47.5634, 42.4338 and 46:2751 mgmL-1, respectively. Compounds 1, 2 and 4 were tested for their antimicrobial properties against seven microorganisms and exhibited the highest activity against B. subtilis, even surpassing the activity of the standard antibiotic Chloramphenicol. They also exhibited antimicrobial activities against P. aeruginosa, S. aureus, C. albicans, and T. mentagrophytes, but were inactive against A. niger and E. coli.